LiBr–LiF‐Rich Solid–Electrolyte Interface Layer on Lithiophilic 3D Framework for Enhanced Lithium Metal Anode. Issue 6 (9th April 2022) - Liu, Ping; Su, Han; Liu, Yu; Zhong, Yu; Xian, Chunxiang; Zhang, Yongqi; Wang, Xiuli; Xia, Xinhui; Tu, Jiangping
Abstract : Metallic lithium anode is considered as an ideal electrode for high‐energy‐density batteries. However, the uncontrollable growth of lithium dendrites, large volumetric change, and interfacial issues during the repeated plating and stripping processes severely hinder its practical applications. Herein, CoO nanosheets‐decorated sponge nickel are synthesized as a host skeleton for thermal‐injected Li (LCN). The conductive 3D matrix serves as a fast electron transfer path to decrease polarization and homogenize the local current density to suppress the Li dendrite. Moreover, the confined framework can relieve the volume change of lithium metal anodes. Furthermore, an artificial LiBr–LiF‐rich solid–electrolyte interface (SEI) layer is constructed at the surface of LCN by the in situ spray‐quenching method. Such an inorganic‐rich SEI provides fast longitudinal Li + transportation and facilitates the uniform deposition of lithium. Accordingly, the SEI@Li/CoO@SN (SLCN) symmetrical cells exhibit a steady overpotential within 35 mV for 1700 h at 1 mA cm −2 /1  cm −2 and achieve high Coulombic efficiency of 99.06% after 150 cycles. Matching with the sulfur cathode, the full cells present promoted rate performance and cycling stability and show a high initial capacity of 1274 mAh g −1 and good capacity retention. Abstract : Herein, a collaborative strategy by combining CoO@SN framework and in situ solid–electrolyte interphase (SEI) engineering to obtain an advanced Li metal anode is discussed. The composite SN skeleton and LiBr–LiF‐rich SEI layer work together to suppress dendrite growth and significantly improve stability and reversibility of Li metal anode. The designed SLCN‐S cells present enhanced rate performance and cycles.